Exploring the Link Between Severe Preeclampsia and Asymptomatic Urinary Tract Infections in the Third Trimester: A Cross-Sectional Study - Bambang Abimanyu; Pribakti Budinurdjaja; M. Robyanoor Ahyadi Radam; Ruth Widhiati Raharjo Putri; Hardyan Sauqi; Hermin Sabaruddin; Agatha Vamela (Berkala Kedokteran, 2025)
Urinary tract infection (UTI) is prevalent in women between 16 and 35 years old. UTI occurs in 2%-7% of pregnant women and affects the inflammatory process, which damages the vascular endothelium by decreasing nitric oxide (NO). This condition is evident in pregnant women with preeclampsia. This research aims to determine the relationship between urinary tract infections and preeclampsia in the third trimester of pregnancy in the delivery room at Ulin Regional Hospital Banjarmasin from January to December 2023. This study's design was cross-sectional observational using secondary data, including patient registers and medical record data. The sample included those who came in with labor, not labor and post-partum conditions for any causes and third-trimester pregnant patients diagnosed with UTI and Severe Preeclampsia in the delivery room of Ulin Regional Hospital, Banjarmasin and use chi-square test for each category. The 119 total pregnant patients with UTI in the third trimester arriving in the delivery room, 73 of them were diagnosed with preeclampsia. Most of them were under 35 yo. A total of 48 patients had multigravida status in all cases of UTI in preeclampsia in the third trimester of pregnancy. The chi-square analysis of the relationship and preeclampsia in pregnant women in the third trimester with p-value of 0.000, and the Odds ratio value was 4.4. Third-trimester pregnant women who suffer from urinary tract infections are 4.4 times more likely to experience preeclampsia.